How law shapes policing: the regulation of alcohol in the U.S., 1750–1860 - Thacher, David (Policing and society, 2020)
Scholars have been skeptical about the capacity of law to shape what police do, but that skepticism results from a myopic view of the relationship between legal systems and policing practices. This paper develops a more holistic view of that relationship by exploring the legal standards, social understandings, and policing practices that played a role in the regulation of alcohol and drunkenness from roughly 1750-1860 in the United States. From the late colonial period through the 1830s, alcohol regulation did not aim to reduce drinking but to prevent public disorder - a task that was well-suited to the character of the early American legal system. From the 1830s through 1860, however, the temperance movement successfully pressed legislators to enact more explicitly moralistic liquor laws, demanding that police ferret out private alcohol sales rather than merely regulating their impact on public order. That new mandate quickly unravelled, for it proved incompatible with a wide range of legal restraints, including traditional protections against searches of private homes, skepticism about the testimony by criminal accomplices, and liability rules related to official enforcement actions. No single restriction on policing tactics undermined antebellum prohibition, but the basic orientation of criminal procedure and the social understandings and practices through which it operated informed a wide range of specific restrictions on morals policing that collectively made prohibition unworkable. To understand that story, we need to take a broader view of the relationship between law and policing than most policing research has taken.